Molecular modeling, synthesis, and antiproliferative evaluation of new isoxazole ring linked by Schiff bases and azo bond - Duha E Taha; Monther F Mahdi; Ayad M. R. Raauf (Wolters Kluwer Medknow Publications, 2023)
Lung cancer is the most common malignancy worldwide, with approximately 1.8 million new cases yearly. Cytotoxic drugs are frequently used in cancer treatment. Even though the medicine enhances patients' quality of life, several drawbacks diminish its efficacy. Drug resistance and many disadvantages associated with chemotherapeutic drug side effects continue to be significant factors limiting the efficiency of cancer treatment. This necessitates developing new effective strategies that target tumors with minimal adverse effects. This research aims to overcome these issues by synthesizing a new series of compounds with an isoxazole ring attached by Schiff bases and azo bonds based on molecular docking with the (Genetic Optimization of Ligand Docking) program and estimating the pharmacokinetic properties with the Swiss ADME. The greatest-fitting compounds were then manufactured and verified by spectral analysis (FT-IR, 1H NMR, and 13C NMR), in vitro MTT assay for assessment of antiproliferative activities against A549 lung cancer cell lines showed that compounds 5a and 5b had an inhibitory concentration half-maximal inhibitory concentration (IC50) (17.34 and 18.32 μM), respectively, which was significantly lower than the inhibitory concentration of erlotinib (IC50 = 25.06 μM).